Progesterone receptor assembly of a transcriptional complex along with activator protein 1, signal transducer and activator of transcription 3 and ErbB-2 governs breast cancer growth and predicts response to endocrine therapy - Díaz Flaqué, María Celeste (2013)
The role of the progesterone receptor (PR) in breast cancer remains a major clinical challenge. Although PR induces mammary tumor growth, its presence in breast tumors is a marker of good prognosis. We investigated coordinated PR rapid and nonclassical transcriptional effects governing breast cancer growth and endocrine therapy resistance.